the penetration of the sacred icon in contemporary tattoo art / Wim Delvoy as a model - Rajaa Kareem Jaboori Alobaidi/ Azher Dakhil Muhsin ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
Tattooing is one of the art of painting practiced by many peoples significantly, and it is an expression of part of their culture open to civilization, and contemporary visual presentations, each of these drawings symbolizes the hidden power, as tattoos have seen a rise in popularity in many parts of the world, especially in North America, southern Japan and Europe. The importance of the research comes through the study of the penetration of the holy icon in contemporary creative tattoo art , and the contemporary artist’s ability to deal with the vocabulary of the Holy according to visions that serve the purposes of open visual presentation , which the contemporary artist seeks.the research relied on the descriptive approach to analyze the research sample models , by previewing the artistic , aesthetic, performance, spatial openness and the study of the penetration of the holy icon in contemporary tattoo art targeted, and concluded the research to a set of conclusions and recommendations.